Anti-N-Methyl-D-Aspartate Receptor Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Universities of Barcelona, Pennsylvania, Oviedo, and Valencia, and the Spanish NMDAR Encephalitis Work Group report the clinical features of 20 pediatric patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis seen in a single center in Spain in the last 4 years.